Penjabaran Soal Ulangan Akhir Semester Genap Mata Pelajaran IPA - -, Juniar Afrida; Diana Nova Santi; Manhaj Aldin; Trirahma Novalia Putri Arfa (Al-Khazini: Jurnal Pendidikan Fisika, 2022)
A test tool is said to be good if the test is valid, reliable, not too easy or too difficult and has different power. If the test items are not analyzed, the question given is not yet known about the condition of the question, it could be that the question is not suitable for use in the exam. The objectives of this research are 1) To analyze the validity of the final exam questions for the even semester science subjects for the 2019/2020 academic year. 2) To analyze the reliability of the final exam questions for even semesters of science subjects at SMP Negeri 2 Beutong. 3) To analyze the level of difficulty of the final exam questions for even semesters of science subjects at SMP Negeri 2 Beutong. 4) To analyze the discriminating power of even semester final exam questions for science subjects at SMP Negeri 2 Beutong. The research method in this study is to use quantitative methods with anates analysis version 4.0. The results of the study were obtained 1) based on data analysis of description questions in class IX of SMP Negeri 2 Beutong it was declared 100% valid or all questions were said to be valid, 2) reliability of descriptions could be said to be reliable at the level of reliability from even semester exam questions in class IX of SMP Negeri 2 Beutong 100% very high reliability, 3) The level of difficulty of the even semester exam descriptions for class IX, has a moderate level of difficulty criteria, there are 6 questions, 2 questions easy criteria and 2 questions very easy criteria. 4) The level of discriminating power of even semester exam descriptions for class IX at SMP Negeri 2 Beutong with the criteria of not discriminating between 2 questions, distinguishing there are 2 questions and very different 6 items.